Pengaruh Kompensasi dan Keselamatan Kerja terhadap Produktivitas Kerja Karyawan pada PT. Musirawas Lestari Makmur, Kabupaten Musi Rawas - Fitria Fitria; Kartini Kartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Human Resources has been recognized as a central force that drives organizational dynamics. This study was conducted to determine the Effect of Compensation and Work Safety on Employee Productivity At PT. Musirawas Lestari Makmur Unit Tuah Negeri Musi Rawas Regency. The sample in this study amounted to 50 employees determined based on simple random sampling technique. Data analysis technique used is Multiple Linear Regression Analysis, Coefficient of Determination (R2), and Test F. From result of Multiple Regression Analysis obtained that compensation (X1) and safety (X2) give contribution of 83,2 percent to work productivity Y). While the rest of 16.8 percent influenced by other variables. which is not included in this study. The results also indicate a significant influence between compensation and work safety on work productivity. For that the company needs to increase the compensation and employee safety to increase employee productivity. Keywords: Compensation, Occupational Safety and Work Productivity